Peran Guru IPS dalam Menanamkan Nilai Sila Kedua Pancasila pada Diri Siswa Kelas VIII SMP di Era Digital - Galuh Viktoni; Sanita Caroline Sasea (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to examine the role of Social Sciences teachers in instilling the character values of the second precept of Pancasila in grade VIII students at SMP Negeri 11 Semarang in the digital era, as well as identify the strategies and challenges faced in the process. This study uses a descriptive qualitative approach. Data were collected through non-participatory observations, semi-structured interviews with social studies teachers and students, and documentation. Data is analyzed using thematic analysis by organizing, categorizing and interpreting findings from various data sources. The results show that social studies teachers play a strategic role in instilling human values through the integration of character values into learning materials, the use of contextual social case discussions related to digital life, role models for teachers, and school culture habituation such as the implementation of the 5S program (smile, greeting, respect, politeness, and friendliness). However, this process faces several challenges, including the influence of uncontrolled social media use, student character differences, and limited parental supervision. Nevertheless, social studies learning contributes positively to strengthening students' empathy, tolerance, and responsible behavior both in real interactions and digital spaces. Therefore, the role of social studies teachers is crucial in developing human and ethical character in the digital era. Keywords: Character Education, Digital Era, Humanitarian Values, Second Principle Of Pancasila, Social Studies Teacher.